Nitrogen Cycling in a Norway Spruce Plantation in Denmark — A SOILN Model Application Including Organic N Uptake - Claus Beier; Henrik Eckersten; Per Gundersen (The Scientific World Journal)
A dynamic carbon (C) and nitrogen (N) circulation model, SOILN, was applied and tested on 7years of control data and 3 years of manipulation data from an experiment involving monthly N addition in a Norway spruce (Picea abies, L. Karst) forest in Denmark. The model includes two pathways for N uptake: (1) as mineral N after mineralisation of organic N, or (2) directly from soil organic matter as amino acids proposed to mimic N uptake by mycorrhiza. The model was parameterised and applied to the data from the control plot both with and without the organic N uptake included. After calibration, the models performance was tested against data from the N-addition experiment by comparing model output with measurements. The model reproduced well the overall trends in C and N pools and the N concentrations in soil solutions in the top soil layers whereas discrepancies in soil-solution concentrations in the deeper soil layers are seen. In the control data, the needle-N concentration was well reproduced except for small underestimations in some years because of drought effects not included in the model. In the N-addition experiment, SOILN reproduces the observed changes; in particular, the changes in needle-N concentrations and the overall distribution within the ecosystem of the extra added 3.5 g N m2 year1 parallel the observations. When organic N uptake is included, the simulations indicate that in the control plot receiving c. 1.9 g N m2 year1, the organic N uptake in average supplies 35% of the total plant N uptake. By addition of an extra 35 kg N ha1 year1, the organic N uptake is reduced to 16% of the total N uptake. Generally, inclusion of the pathway for organic N uptake improves model performance compared with observations for both C and N. This is because mineral N uptake alone implies a larger mineralisation rate, leading to bigger concentrations of N in the soil and soil water, bigger N losses, and net loss of c. 100 kg C ha1 year1, thereby causing depletion of the organic soil layer.